JORDANIAN LITERACY EDUCATION: SHOULD WHOLE LANGUAGE BE IMPLEMENTED? - Alhaddad, Abdelkareem Saleem (European Scientific Journal, ESJ, 2014)
This paper aims to clarify and discuss the extent to which the wholelanguage approach might be implemented to literacy education in Jordan. The researcher describes what the whole-language approach is all about, what whole language opponents’ view and what proponents are trying to say. Therefore, the researcher introduces and discusses whole-language principles and activities. Then, the requirements for implementing the whole-language approach in Jordan are clarified.